Assessment of present awareness on reproductive health and evaluation of a tool designed for reproductive health education among school going adolescent girls - A., Vanusha; K., Parvathavarthini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Reproductive health is an important area of concern in adolescent health. Assessment of unmet needs of unmarried adolescent girls during past five years revealed the felt needs are mostly unmet in areas related to menstrual hygiene, knowledge on consequences of early marriage, risk of teenage pregnancies, sexually transmitted infections, HIV and AIDS, unsafe abortions and breast feeding. This study is carried out to assess the knowledge of adolescent girls regarding menstruation, pregnancy, contraception, STD’s, AIDS, and breast feeding and to study the effect of health education program in terms of improvement in their knowledge. Methods: This study was carried out among adolescent girls from randomly selected government girls higher secondary schools of Pondicherry from class 8 to class12. A total of 300 students were included in the study. A pretested questionnaire (English/Tamil) was administered to students. This was followed by an interactive session with the students to clarify doubts. Students was asked to fill an immediate post-test questionnaire to evaluate the effect of intervention (health education). After a minimum period of six months the students was reassessed by a same pretest and post-test questionnaire. Results: There was a statistically significant improvement in knowledge scores in various aspects of reproductive health following periodic health education intervention program. Conclusions: The knowledge on reproductive health and responsible sexual behaviour among school going adolescents is inadequate. Appropriate strategy to reach this vulnerable group has to be formulated by health care professionals with coordination and support from school authorities.